Serum zinc and copper levels in alopecia - Rahman, Farhana; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2019)
Background: Emerging evidence suggests that trace elements such as zinc (Zn2+) and copper (Cu2+) are essential cofactor for multiple enzymes and have functional activities within hair follicles. So its deficiencies may cause hair loss. Objective: To assess the serum zinc and copper levels in alopecia. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from January to December during 2017. Thirty five patients icluding both sexes with hair loss aged 18 to 45 years were study group and 35 ages and BMI matched healthy subjects were control group. Serum zinc and copper levels were estimated by flame atomic absorption spectrophotometry. For statistical analysis Unpaired Student’s‘t’ test and Chi square tests were performed. Results: Serum Zn2+ and Cu2+ levels were significantly (p<0.001) lower in study group than those of control group. Conclusions: It was concluded that serum Zn2+ and Cu2+ deficiencies are associated with hair loss patients. J Bangladesh Soc Physiol. 2019, June; 14(1): 21-25